INTERLEXICAL RELATIONS IN ENGLISH STRESS - Kumashiro, Fumiko; Kumashiro, Toshiyuki (International Journal of English Studies, 2009)
In this paper, we propose a cognitive, non-reductionist analysis of English stress as it pertains to interlexical relations, based on the usage-based model as proposed by cognitive grammar and on the connectionist interactive activation model. We claim that interlexical relations involved in English stress can felicitously be accounted for by employing actually-occurring expressions as constraints and that precise explication of these relations requires consideration of not only phonological but also semantic factors. In the course of making these claims, we attempt to demonstrate that cognitive grammar, being a usage-based, non-reductionist framework, can accommodate actually-occurring expressions as constraints in a coherent manner and further that the theory can naturally bring semantic factors to bear on phonological analyses, being a non-modular, unificational framework